A critical introduction to phonology functional and usage-based perspectives - Silverman, Daniel Doron 1963- (London, UK Bloomsbury Academic, 2017)
Taking an interdisciplinary approach to phonological theory and analysis, A Critical Introduction to Phonology introduces the key aspects of the discipline. Departing from the mainstream tradition, Daniel Silverman argues that the nature of linguistic sound systems can only be understood in the context of how they are used by speakers and listeners.By proposing that linguistic sound systems are the product of an interaction among sound (acoustics), mind (cognition), and body (physiology), Silverman focuses on the functional consequences of their interaction. Now with each chapter supplemented by a section on Doing Phonology , together with phonological examples from a large corpus of data, this expanded second edition offers a provocative introduction to phonological theory. This book is essential reading for all students and researchers of phonology who are already familiar with the standard approaches and provides both a new theoretical background and the mechanical tools for truly successful phonological analyses.
Machine generated contents note: -- Introduction -- Part I -- 1. Three Types of morph selection -- Doing phonology 1: introduction to the "F-tube," and data analysis -- Further reading -- 2. Meaning-changing morph selection -- Doing phonology 2: data analysis -- Further reading -- Part II -- 3. Homophone-deriving morph selection -- Doing phonology 3: data analysis -- Further reading -- 4. Heterophone-maintaining morph selection -- Doing phonology 4: data analysis -- Further reading -- 5. Variation and probability -- Doing phonology 5: data analysis -- Further reading -- 6. The pull of phonetics; the push of phonology -- Doing phonology 6: data analysis -- Further reading -- Part III -- 7. Loquor ergo es -- Further reading.
Previous edition: 2006.
Includes bibliographical references and index.
Keywords: Grammar, Comparative and general -- Phonology